Effect of Greenhouse Gas Emissions, Renewable Energy Utilization, CSR Expenditures, and Green Finance on Financial Performance in the Energy Sector for the Period 2021–2023 - Anfila Catur Berliana; Ridarmelli, Ridarmelli (Green Publisher Indonesia, 2025)
This study examines the impact of greenhouse gas emissions, renewable energy usage, Corporate Social Responsibility (CSR) expenditure, and green finance on the financial performance of energy companies in Indonesia. Using multiple regression analysis, this research employs secondary data extracted from the annual reports of energy companies listed on the Indonesia Stock Exchange for the period 2021–2023. The findings reveal that greenhouse gas emissions and renewable energy usage have a significant negative effect on financial performance, indicating that higher emissions and increased reliance on renewable energy are associated with lower profitability. Conversely, CSR expenditure exhibits a significant positive effect, suggesting that greater investment in social responsibility enhances financial performance. Meanwhile, green finance does not demonstrate a significant influence on financial performance. These results provide valuable insights for mining companies in formulating sustainable and responsible business strategies while contributing to the broader discourse on the nexus between sustainability and corporate financial performance.